Konten Seni Lukis dalam TikTok sebagai Ekspresi Budaya Populer Remaja Urban - Fania, Dwi; Fajrie, Mahfudlah; Muslimin, Khoirul (Mu'ashir: Jurnal Dakwah dan Komunikasi Islam, 2025)
Technological advances make it a human need to express themselves and form self-actualization through TikTok social media, such as sharing painting content in the era of modernization. The purpose of this research is to find out the existence of painting content and personal branding through TikTok as popular culture. This research uses a qualitative method with a virtual ethnography approach to the AMS (Cyber Media Analysis) model by Rulli Nasrullah, including 4 levels, namely, media space, media documents, media objects, and media experiences. Data collection techniques in this study through observation and documentation on TikTok accounts @erikarichardo, @rhmatdraw, and @dyssayangkamu. The results of the research through the AMS model found that the selection of TikTok is a good choice as a medium for self-expression through painting content because it has various features and its reach is wide open. In the era of digitalization, making painting as part of popular culture provides an excellent opportunity for artists and painting creators to build a reputation, create works that are attractive, known, and liked by many people.